Diagnosis and Treatment of Patients with Autoimmune Hepatitis (Experts’ Agreement) - Yu. G. Sandler; E. V. Vinnitskaya; K. L. Raikhelson; K. V. Ivashkin; S. N. Batskikh; E. N. Aleksandrova; D. T. Abdurakhmanov; D. I. Abdulganieva; I. G. Bakulin; A. O. Bueverov; S. L. Vorobyev; O. A. Gerasimova; et al. (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
Background. In the last decade, the understanding of the pathogenesis of autoimmune hepatitis (AIH) has significantly deepened, based on the results of new clinical studies some diagnostic issues have been revised and immunosuppressive therapy regimens have been optimized.Materials and methods. The latest Russian clinical guidelines for the diagnosis and treatment of AIH were presented in 2013; and in 2017, the first Russian agreement on the diagnosis and treatment of AIH was held. Updating approaches to the management of patients with AIH necessitated next systematization for use in clinical practice. In February 2024, the final session was held to discuss the provisions of the second agreement on the diagnosis and treatment of AIH.Results. This publication presents the main discussion points of the agreement regarding methods and algorithms for detecting autoantibodies, the role of liver biopsy, revised morphological criteria for AIH, optimized immunosuppressive therapy regimens, updated criteria for assessing the response to therapy.Conclusions. The agreement was the result of the work of a group of experts on the diagnosis and treatment of AIH and represents the basis for the creation of updated federal clinical guidelines.